Fleece yield and characteristics of norduz sheep - Orhan Yılmaz; Hüseyin Denk (Eurasian Journal of Veterinary Sciences)
This study was carried out to investigate fleece yield and characteristics of Norduz sheep. Fifty-seven ewes and 14 rams were used in this study. Greasy fleece weight, fiber diameter, fiber length, fiber elasticity, breaking strenght, me-dullated fiber, kemp fiber, clean fleece percentage and effects of some environmental factors on the these characteristics have been also studied. Least squre method was used in the statistical analysis. Comparison of means was based on the Duncan's multiple range test. Least squares means for greasy fleece weight (kg), fiber diameter (p), fiber length (cm), fiber elasticity (%), breaking strenght (g), medullated fiber (%), kemp fiber (%) and clean fleece percentage (%) were 2.91, 37.51, 6.89, 32.71,13.71, 7.50,1.81 and 68.25, respectively. Effects of age (P<0.01) and sex (P<0.Q01) on greasy fleece weight were significant, but the effect of body weight at shearing on greasy fleece weight was not significant (P>0.05). Effects of age, sex and body weight did not have a significant on fiber length, kemp fiber percentage and clean fleece percentage (P>0.05). Effects of age (P<0.001) and body weight at shearing (P<0.05) on fiber diameter were significant, but the effect of sex on fiber diameter was not significant (P>0.05). Effect of age on fiber elasticity and breaking strenght was significant (p<0.05), but effects of sex and body weight at shearing on fiber elasticity and breaking strenght were not significant (P>0.05). Medullated fiber was affected by age and sex (P<0.05), but the effect of body weight at shearing on medullated fiber was not significant (P>0.05).